Analisis Lokasi Prioritas Ruang Terbuka Hijau Berbantuan Sistem Informasi Geografis di Kecamatan Pamekasan Kabupaten Pamekasan - Habibi, Ahmad; Utaya, Sugeng; Primandani, Rr Siti Masrihati (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2024)
Urbanization has caused Pamekasan Sub-district to experience obstacles in meeting the minimum requirement of Green Open Space area in accordance with the established regulations. This research aims to determine the priority location of Green Open Space by integrating multi parameters (NDVI, THI, and Population Density) with the help of Geographic Information System so that Green Open Space development planning can run effectively. The results of the analysis are then compared with the RDTR of Pamekasan Urban Area to ensure appropriate planning implementation. The results of the three analyses state that there are 62% of areas that are highly prioritized for green space development. The results of the comparison of the RTH priority map according to Humaidah with the spatial pattern map of the Pamekasan Urban RDTR show a 76% conformity and there are still 24% that are not suitable, including the types of RTH for cemeteries, sub-district parks, and urban forests.